2012
DOI: 10.1136/bmj.e6226
|View full text |Cite
|
Sign up to set email alerts
|

Tocolytic therapy for preterm delivery: systematic review and network meta-analysis

Abstract: Objective To determine the most effective tocolytic agent at delaying delivery.Design Systematic review and network meta-analysis. Study selection Randomised controlled trials of tocolytic therapy in women at risk of preterm delivery. Data sources Data extractionAt least two reviewers extracted data on study design, characteristics, number of participants, and outcomes reported (neonatal and maternal). A network meta-analysis was done using a random effects model with drug class effect. Two sensitivity analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
242
1
17

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 357 publications
(272 citation statements)
references
References 109 publications
(68 reference statements)
2
242
1
17
Order By: Relevance
“…Our failure to replicate this finding may well be a result of our small sample size; the confidence interval includes the benefit of nifedipine seen in the meta-analysis. Two previous meta-analyses have suggested nifedipine is superior to terbutaline in terms of prevention of neonatal adverse events, although they failed to show a difference in these events between nifedipine and placebo [22,24] while the network meta-analysis [6] failed to find differences 3 Median and interquartile range. 4 Mann-Whitney U-test.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Our failure to replicate this finding may well be a result of our small sample size; the confidence interval includes the benefit of nifedipine seen in the meta-analysis. Two previous meta-analyses have suggested nifedipine is superior to terbutaline in terms of prevention of neonatal adverse events, although they failed to show a difference in these events between nifedipine and placebo [22,24] while the network meta-analysis [6] failed to find differences 3 Median and interquartile range. 4 Mann-Whitney U-test.…”
Section: Discussionmentioning
confidence: 91%
“…The most compelling summary of results of previous trials thus far comes from a network meta-analysis examining all the randomized trials of all agents used for tocolysis [6]. This meta-analysis found that, in comparison with terbutaline, calcium channel blockers have a higher probability of achieving delay in delivery beyond 48 hr.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The commonly used tocolytics are Beta-2 agonists (isoxsuprine hydrochloride, terbutaline sulfate and ritodrine hydrochloride), calcium channel blockers (nifedipine), oxytocin receptor antagonists (atosiban), prostaglandin synthetase inhibitors, magnesium sulfate and nitric oxide donors. [8][9][10] They act through various mechanisms to decrease the availability of intracellular calcium ions, leading to inhibition of actin-myosin interaction. 5 Pertinently, the management of PTL has been plagued by a low success rate along with the incidence of serious side-effects arising from the use of therapeutic approaches, more so with beta-mimetic tocolytics.…”
Section: Introductionmentioning
confidence: 99%